2001
DOI: 10.1080/j.1600-0412.2001.080003251.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms in late pregnancy and postpartum

Abstract: Background. Postnatal depression refers to a non-psychotic depressive episode that begins in or extends into the postpartum period. The aims of this study were to examine the prevalence of depressive symptoms in a pregnant and later postnatal population, to determine the natural course of these symptoms and whether there is an association between antenatal and postnatal depressive symptomatology. Methods. A longitudinal study with a total population of 1,558 consecutively registered pregnant women in the south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
1
20

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(157 citation statements)
references
References 9 publications
11
125
1
20
Order By: Relevance
“…Critically, unlike our original study and the data set generated by Mehta et al, these results demonstrate that our model may be efficacious in a general population sample without a history of mood disorder. It is of note that only a small number (2.1%) of women developed depressive symptoms postpartum compared with the reported averages of 10-20% (Josefsson et al, 2001;Miller, 2002;Pearlstein et al, 2009). Permutation analyses increase the confidence that the high AUC values observed are not a result of small numbers of cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Critically, unlike our original study and the data set generated by Mehta et al, these results demonstrate that our model may be efficacious in a general population sample without a history of mood disorder. It is of note that only a small number (2.1%) of women developed depressive symptoms postpartum compared with the reported averages of 10-20% (Josefsson et al, 2001;Miller, 2002;Pearlstein et al, 2009). Permutation analyses increase the confidence that the high AUC values observed are not a result of small numbers of cases.…”
Section: Discussionmentioning
confidence: 98%
“…Postpartum depression (PPD) affects between 10 and 20% of women (Josefsson et al, 2001;Miller, 2002;Pearlstein et al, 2009) and has significant effects on both mother and child (Breese McCoy, 2011;Cuijpers et al, 2008;Field, 2011;Hirst and Moutier, 2010;O'Hara, 2009;Soufia et al, 2010). Certain populations have higher rates of PPD including 30% in women with a history of depression and 52% of women with bipolar disorder (Viguera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…124,125 After delivery, an activation of the type 1 response of the maternal immune system takes place. 126,127 This type 1-dominated maternal immune re-balancing was found to be associated with the postpartum blues, 126 a state found in 20-75% of mothers, 128,129 or the postpartum depression, a state found in 10-15% of mothers. 130 After delivery, an increase of the proinflammatory immune response was described.…”
Section: The Inflammatory Hypothesis Of Depressionmentioning
confidence: 96%
“…The prevalence of antenatal anxiety during the third trimester is reported to be between 10 and 24% and it also overlaps with depression and increases the risk of postnatal depression (Sutter-Dally et al 2004;Heron and O'Connor 2004). Around 13-17% of women suffer from depressive illness during pregnancy and or the first year postpartum (Josefsson et al 2001). Clinical experience has shown that the number of women who state fear of injections, blood and hospital environments has increased.…”
Section: Introductionmentioning
confidence: 99%